Statistics for death and injury on the roads: what do they tell us about risk and safety engineering? - Reinhardt-Rutland, A.H. (2002)
A reasonable strategy for reducing road casualities should reside in safety engineering: seat-belts; airbags; ABS braaakes; water-repellent road-surfaces; and the like. Yet, for some time there have been rumblings about whether engineering initiatives are ever effective over the long term. One crucial issue that has emerged concerns the intgerpretation of trends in casualty rates; the present article is directed primarily to this issue and, specifically, to what appears to be a paradox in the relationship between death and injury statistics. - Reproduced.
Keywords: Accidents; Transport safety